Impact Skills Human Capital in Context of Human Resources in Drug Cases in The Kampar Research Unit (Three Pillar Approach) - Muhammad Adil. MA; Abshor Marantika; Supardi Supardi (Dinasti International Journal of Education Management and Social Science, 2025)
This study aims to analyze the dynamics of collaboration, the forms of collaboration, and the forms of drug prevention through the roles of the three pillars (government, security forces, and the community) in Kampar Regency. This study uses a quantitative approach supported by qualitative data through interviews, questionnaires, and documentation. Data were obtained from questionnaires distributed to respondents related to drug prevention efforts. Then, they were analyzed using quantitative descriptive techniques supported by academic discussions based on communication management theory, deterrence theory, and regulations of the National Narcotics Agency (BNN). The research results show that drug control in Kampar Regency has been carried out through five main aspects: promotive, preventive, curative, rehabilitative, and repressive. This study concludes that the effectiveness of drug control in Kampar Regency is significantly influenced by the quality of collaboration across the three pillars. Good synergy fosters strategic integration, but challenges remain, including limited rehabilitation facilities, reliance on repressive approaches, and suboptimal use of technology in prevention. These findings offer important implications for local governments and the National Narcotics Agency (BNN) in formulating collaborative policies and strengthening data and service integration.